2020
DOI: 10.1186/s12879-020-4875-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model for bacterial late-onset neonatal sepsis in a tertiary care hospital in Thailand

Abstract: Background: Early diagnosis of neonatal sepsis is essential to prevent severe complications and avoid unnecessary use of antibiotics. The mortality of neonatal sepsis is over 18%in many countries. This study aimed to develop a predictive model for the diagnosis of bacterial late-onset neonatal sepsis. Methods: A case-control study was conducted at Queen Sirikit National Institute of Child Health, Bangkok, Thailand. Data were derived from the medical records of 52 sepsis cases and 156 non-sepsis controls. Only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 66 publications
6
17
1
2
Order By: Relevance
“…According to maternal factors, It was found no significant difference between septic cases and controls in terms of maternal age, maternal diseases, maternal medications, maternal exposure to radiation or smoking, fever in pregnancy, previous abortion, still birth and family history (p > 0.05). These results were in accordance with (Husada et al, 2020) findings [ 17 ] and on the contrast with (Siakwa et al, 2014) [ 18 ] who showed that the maternal factors were significantly associated with neonatal sepsis.…”
Section: Discussionsupporting
confidence: 92%
“…According to maternal factors, It was found no significant difference between septic cases and controls in terms of maternal age, maternal diseases, maternal medications, maternal exposure to radiation or smoking, fever in pregnancy, previous abortion, still birth and family history (p > 0.05). These results were in accordance with (Husada et al, 2020) findings [ 17 ] and on the contrast with (Siakwa et al, 2014) [ 18 ] who showed that the maternal factors were significantly associated with neonatal sepsis.…”
Section: Discussionsupporting
confidence: 92%
“…For the outcome, most of died subjects had junior high school and senior high school mother education, neither bachelor mother had no died subjects. This finding also similar with Husada et al was found low educated mother were risk factor of neonatal LOS (78%) [12].…”
Section: Discussionsupporting
confidence: 90%
“…In addition Umate et al was found lethargic (68.75%) and respiratory distress (72.60%). Temperature instability and seizure also found as independent factors associated with serious CNS complication [12][13][14]. That statement is strengthened by our results in which there was no temperature instability (96%) neither seizure (96%) most of our subjects had good outcome (70%).…”
Section: Discussionsupporting
confidence: 74%
“…Klebsiella pneumoniae and CONS were the most common microorganisms. These data were comparable with other developing countries [49,50,51] in LONNS.…”
Section: Discussionsupporting
confidence: 86%